Association between Hypertension and Epistaxis: Systematic Review and Meta-analysis. (December 2017) - Min, Hyun Jin; Kang, Hyun; Choi, Geun Joo; Kim, Kyung Soo
Objective: Whether there is an association or a cause-and-effect relationship between epistaxis and hypertension is a subject of longstanding controversy. The objective of this systematic review and meta-analysis was to determine the association between epistaxis and hypertension and to verify whether hypertension is an independent risk factor of epistaxis. Data Sources: A comprehensive search was performed using the MEDLINE, EMBASE, and Cochrane Library databases. Review Methods: The review was performed according to the Meta-analysis of Observational Studies in Epidemiology guidelines and reported using the Preferred Reporting Items for Systematic Reviews and Meta-analysis guidelines. Results: We screened 2768 unique studies and selected 10 for this meta-analysis. Overall, the risk of epistaxis was significantly increased for patients with hypertension (odds ratio, 1.532 [95% confidence interval (CI), 1.181-1.986]; number needed to treat, 14.9 [95% CI, 12.3-19.0]). Results of the Q test and I 2 statistics suggested considerable heterogeneity (P χ 2 = 0.038, I 2 = 49.3%). The sensitivity analysis was performed by excluding 1 study at a time, and it revealed no change in statistical significance. Conclusion: Although this meta-analysis had some limitations, our study demonstrated that hypertension was significantly associated with the risk of epistaxis. However, since this association does not support a causal relationship between hypertension and epistaxis, further clinical trials with large patient populations will be required to determine the impact of hypertension on epistaxis.